COVID-19, psychosocial issues, politics, and public mental health care. (June 2021) - Pillay, Anthony L; Kramers-Olen, Anne L
The COVID-19 pandemic heralded challenges that were both significant and unfamiliar, placing inordinate burdens on health care systems, economies, and the collective psyche of citizens. The pandemic underscored the tenuous intersections between public mental health care, politics, economics, and psychosocial capital. In South Africa, the inadequacies of the public health system have been laid bare, and the disproportionate privileges of the private health care system exposed. This article critically considers government responses to the COVID-19 pandemic, the psychosocial correlates of lockdown, politics, corruption, and public mental health policy in South Africa.